Penegakan Hukum Pidana Terhadap Pemalsuan Identitas Profesi Dokter Gigi yang Melakukan Tindakan Medik di Kota Kupang - Maria Elfriany Clarita Siu; Heryanto Amalo; Darius A. Kian (Lembaga Pengembangan Kinerja Dosen, 2024)
The purpose of this research is to analyze law enforcement and what are the modus operandi for committing a crime. The research method used is empirical juridical research obtained from interviews conducted at Kupang City Police Station and data collection at Kupang District Court. It also includes secondary data obtained by the author from books, articles, journals, laws and regulations, and others that are relevant and support this research. The results showed that the modus operandi carried out by the perpetrator of falsifying the identity of the dentist profession who performs medical actions is that the perpetrator uses medical devices, promotes himself by going to people's homes, uses methods similar to dentists, uses a dentist's identity tag complete with his title. Law enforcement carried out by the police and courts in the form of investigations and investigations as well as prosecutions and trials.